Work related stress and wellbeing in critical care nurses and their relationship with patient safety - McCallum, Carol Louise (University of Dundee, 2022)
Background: In the United Kingdom 2,460 per 100,000 nurses reported high work stress (Health & Safety Executive, 2020). The prevalence of work stress in critical care nurses (CCNs) is unknown. Despite a large literature base, the causes, and consequences of CCN work stress cannot be determined. Little is known of the effects of CCN work stress on patient outcomes.

Methods: Phase I explored the work-related stress literature and identified measures to capture work-related stress and wellbeing in CCNs using the Job Demand-Resources (JD-R) model (Demerouti et al., 2001) as an underpinning framework. In phase II tested the preliminary data collection instrument to evaluate its psychometric and statistical performance and the main study protocol. In phase III, main study, the psychometric adequacy, and dimensionality of items were examined using exploratory and confirmatory factor analysis. Penalised regression models identified CCN and unit level predictors of health impairment and motivation. Penalised regression will determine how job demands, job resources and personal resources interact to influence health impairment and motivational outcomes. Finally, exploratory mediation analysis will be applied to explore the mediation potential of health impairment outcomes in the relationship between job demands and organisational outcomes, and separately motivational outcomes in the relationship between job resources and performance outcomes.

Results: Phase I, found a large and atheoretical literature. Work stress in CCNs was poorly conceptualised, and findings were inconsistent. Many potential predictors and consequences of work stress were evident. The JD-R model, emerged as a suitable framework, and it was operationalised using theoretically determined measures (chapter 2 and 3). In phase II, these measures performed adequately (N=54), and the data collection instrument was reduced, from 61 (340-items) to 41 subscales (231 items) for phase III. No protocol changes were required.

In Phase III: Participants (N=557; 19 ICUs; Response Rate = 47%) were female (90.1%), average of 40.37 years old, married (54.4%), with children (58.1%) and a mean of 11.72 years critical care nursing experience. Most had a Bachelor's degree (68.8%) and a post registration critical care qualification (53.6%). Items used to measure specific JD-R model concepts, each share one dimension (unidimensional). All concepts except 'motivational outcomes' show convincing multidimensionality although this does not consistently translate into reliable measurement of these subscales. Bifactor models provide optimal fit, except for job demands and job resources where theoretical models are best. Job demands and job resources have a complex factor structure.

Work stress is problematic. 'Emotional Exhaustion' is highly prevalent for nearly a quarter, yet 'Depersonalisation' is low for more than two-thirds, and two-fifths report low 'Personal Accomplishment'. Psychological distress is high for one third. Motivation is of moderate prevalence. 'Work Engagement' is moderate for over two-thirds, and 'Dedication' is high for one-fifth, yet only one tenth is highly invigorated and absorbed.

Only two CCN variables, 'Childlessness' and 'Poor Professional Development Opportunities' were associated with 'Emotional Exhaustion'; yet, having children, higher nursing grade, working full time, working overtime, with infrequent redeployment, fewer absence occasions, a Bachelor's degree and more professional development opportunities were associated with high 'Dedication' and 'Vigour'. No unit level variables were associated with health impairment or motivational outcomes.

Highest job demands arose from 'Mental Load; 'Physical Effort' and 'Emotional Load', with others being moderately demanding. Job resources that were important were 'Learning Opportunities', 'Autonomy' and social/instructional support from 'Supervisors' and 'Colleagues'. Lower rated resources included those that suggest issues with leadership and management, and those that were related to organisational or employment resources. This has implications for how organisations support and resource CCN provision.

Overall high job demands were associated with increased health impairment, low job resources are associated with increased motivation. Only one interaction was found whereby, when 'Negative Affect' is high, it moderates the relationship between 'Role Conflict' and 'Psychological Distress' and increases 'Psychological Distress'.

Finally, there were two main mediation effects whereby when job demands are high and health impairment is high, poor organisational outcomes result. When job resources are high and work engagement is high, good organisational outcomes occur.

Conclusion: These are exploratory findings, cause and direction cannot be determined using cross-sectional data. These data suggest that a key findings is that CCN wellbeing can influence organisational outcomes in particular patient safety and quality of care. If organisations wish to improve patient care outcomes, they ought to seriously consider and intervene to enhance nurse wellbeing. Further longitudinal studies are required to understand psychological mechanisms underlying these findings